The art in policy Delphi practice: critical decisions for its design and application on foresight exercises - Vicente-Oliva, Silvia (Acciones e Investigaciones Sociales, 2025)
The Delphi method was initially developed in the mid-20th century as a tool for exploring future technological developments, and its variant known as the policy Delphi was developed in 1970 to incorporate the ideas of different stakeholder groups in foresight exercises. A review of more than one hundred exercises that employed this technique up to 2025 allows for a reflection on its practical implementation and on the crucial decisions involved during its design, execution, and analysis phases. Fourteen crucial decisions have been identified for the design, execution, as well as the analysis and interpretation of foresight exercises, which concern the balance in areas such as theoretical considerations, participation of all stakeholder groups,  uncertainty management, breadth of analysis, methodological approaches, the use of collective expertise to examine policy instruments and decisions, case-based experiences, and decision-making informed by dominant patterns of thought.
Keywords: Foresight; Futures; Project Design; Methods